2016
DOI: 10.1016/j.jcin.2015.12.267
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Coated Balloons for Complex Femoropopliteal Lesions

Abstract: These results suggest that DCB are safe and effective in delaying rather than preventing restenosis in long, complex lesions and restenosis of the femoropopliteal tract. Further studies are recommended to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
140
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(152 citation statements)
references
References 25 publications
10
140
0
2
Order By: Relevance
“…In the present 37 patients undergoing re-EVT, the 2-year primary patency was 58%, which was similar to a previous report. 7 As well, we showed that the results of POBA or BNS for DCB restenosis were discouraging for either ISR or non-ISR lesions. The rates of freedom from binary restenosis and CD-TLR at 1 year were 14% and 38%, respectively.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…In the present 37 patients undergoing re-EVT, the 2-year primary patency was 58%, which was similar to a previous report. 7 As well, we showed that the results of POBA or BNS for DCB restenosis were discouraging for either ISR or non-ISR lesions. The rates of freedom from binary restenosis and CD-TLR at 1 year were 14% and 38%, respectively.…”
Section: Resultsmentioning
confidence: 64%
“…7 Re-EVT in 30% of the participants in Schmidt's study was necessary to maintain vessel patency, but the outcome and treatment strategy in cases of re-EVT have not been reported. 7 Iida et al reported their 1-year results of re-EVT for DES-ISR of the FP artery. They showed a higher rate of restenosis after reintervention regardless of focal, diffuse or occluded lesions (53%, 74%, and 78%, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6] In addition to improved efficacy in terms of improvement of symptoms, time free from reintervention, and reductions in amputation rates, studies have also shown that the procedures have similar levels of safety, which is understandable considering the similar techniques employed.…”
Section: Discussionmentioning
confidence: 99%
“…Up to date, it is the long lesions and chronic total occlusions of the femoropopliteal artery that continue to represent a major challenge for currently available endovascular treatment approaches. In case of intermediate and long femoropopliteal lesions, stenting with conventional or drug-eluting (long) nitinol stents ("full metal jackets") did not show convincing patency rates, but was associated with relevant in-stent-restenosis rates [6][7][8]. Therefore, on the one hand, non-stent-based approaches ("leave nothing behind" strategy) would be particularly desirable for long lesions.…”
Section: Discussionmentioning
confidence: 99%